2014
DOI: 10.31482/mmsl.2014.025
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted and Ct Navigated Reposition of an Orbital Blow-Out Fracture

Abstract: One possible use of CT navigated surgery in Otorinolaryngology includes traumatology of the facial skeleton. CT navigation enables a surgeon to assess the range and quality of reposition and fixation of a fracture, in our case the fracture of the orbital floor, using a navigated tube. We proceed from pre-operative CT of the paranasal sinuses images to navigation with 1,5-2,0 mm incisions and subsequent registration. Formerly, we used mainly transantral approach at our department, while currently we prefer subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Two weeks are enough for the orbital hematoma and edema to subside or reduce and to prepare the patient for surgery Kwon et al divided orbital floor fractures into anterior, posterior and anteroposterior 12 . But there is a very large dispersion of functional results, 8.7-67%, especially in the persistence of postoperative diplopia 5,7,[13][14][15][16][17] . Worth noting is the contribution of CT-guided surgery, leading to the complete disappearance of postoperative diplopia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two weeks are enough for the orbital hematoma and edema to subside or reduce and to prepare the patient for surgery Kwon et al divided orbital floor fractures into anterior, posterior and anteroposterior 12 . But there is a very large dispersion of functional results, 8.7-67%, especially in the persistence of postoperative diplopia 5,7,[13][14][15][16][17] . Worth noting is the contribution of CT-guided surgery, leading to the complete disappearance of postoperative diplopia.…”
Section: Discussionmentioning
confidence: 99%
“…The first functional results with CT navigation were not published until 2014 (ref. [5][6] . Beumer, Pham and Schramm [18][19][20] recommend the use of CT navigation in maxillofacial bone fractures to minimize post-traumatic enophthalmos and for improved facial symmetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of our previous retrospective study, we identified two critical volumes for indicating surgical treatment in blow-out fractures: 500 mm 3 in anterior and posterior fractures and 1400 mm 3 in anteroposterior fractures. We focused on the creation of new quantitative indication criteria for surgical therapy by calculating the volume of proplapsed soft tissues of the orbit and determining the critical values 3,4 .…”
Section: Introductionmentioning
confidence: 99%